Metadiscourse and dialogical relationships in a virtual learning environment - Francisca Henrique Jesus, Josefa (Seven Editora, 2023)
This work analyze the presence of metadiscourse in the dialogues formed between the subjects in a Virtual Community of Learning and Practice (VCOP). The focus of analysis is the metadiscursive markers present in the clippings of dialogues collected in two discussion forums that deal with orientations, clarifications and didactic-pedagogical and academic information from the undergraduate course in Letters-Portuguese Language, in the distance learning modality. The theoretical approach is based on Behar (2009), Litto; Formiga (2012), who discuss pedagogical models, technological advances and innovations for distance education, and in Bakhtin ([1975] 2010; [1979] 2003), Hyland (1998a; 1898b), Hyland and TSE (2004), who treat language as strategies for interaction in discourse, emphasizing its dialogical and interpersonal character. The study hopes to contribute to the reflection that metadiscursive markers are essential textual elements for the interaction and systematization of interpersonal relationships to be strengthened in the virtual learning environment. DOI: https://doi.org/10.56238/tfisdwv1-091